N-Glycosidase activity in extracts of Bacillus subtilis and its inhibition after infection with bacteriophage PBS2. - Friedberg, E C (1975)
We have detected in crude extracts of Bacillus subtilis an N-glycosidase activity which catalyzes the release of free uracil from DNA of the subtilis phage PBS2 labeled with [3H]uridine. This DNA contains deoxyuridine instead of thymidine. The enzyme is active in the presence of 1.0 mM EDTA and under these conditions Escherichia coli or T7 DNA labeled with [3H]thymidine is not degraded to labeled acid-soluble products. The activity resembles an N-glycosidase from E. coli which releases free uracil from DNA containing deaminated cytosine residues. Both enzymes in crude extracts are active in the presence of EDTA, do not require dialyzable co-factors, and have the same pH optimum. They differ in that the enzyme from E. coli is more sensitive to heat, sulfhydryl reagents, and salt. The enzyme from B. subtilis is inactive on DNA containing 5-bromouracil or hydroxymethyluracil. Extracts of PBS2-infected B. subtilis lose the N-glycosidase activity within 4 min after infection and contain a factor that inhibits the N-glycosidase activity within 4 min after infection and contain a factor that inhibits the N-glycosidase activity in extracts of uninfected cells in vitro.